Dorsolateral prefrontal cortex dysfunction caused by a go/no-go task in children with attention-deficit hyperactivity disorder: A functional near-infrared spectroscopy study - Wu, Ting; Liu, Xiaoli; Cheng, Fang; Wang, Shuai; Li, Chang; Zhou, Dongsheng; Zhang, Wenwu (Frontiers in Neuroscience, 2023)
Background: Children with attention deficit hyperactivity disorder (ADHD) exhibit executive function deficit which is supposed to be related to prefrontal regions dysfunction. Our study aims to evaluate the alteration of brain activation in children with ADHD during a go/no-go task using functional Near Infrared Spectroscopy (fNIRS) in comparison to the typically developing (TD) children. Methods: 32 children with ADHD and 31 typically developing(TD) peers performed a go/no-go task with measurements of averaged oxygenated hemoglobin signal changes (△avg oxy-Hb) in the prefrontal lobe with fNIRS. Results: fNIRS data showed significantly differences in the left and right dorsolateral prefrontal cortices, and lower △avg oxy-Hb change (right DLPFC mean=-0.044,SD=0.034,p=0.021; left DLPFC mean=-0.011,SD=0.031,p=0.025)in ADHD group compared with normal controls. Conclusions: Our results indicate that inhibitory dysfunction in children with ADHD was related to functional impairments of the dorsolateral prefrontal cortex. The go/no-go task used with fNIRS may be one useful measurement to assess prefrontal brain dysfunction in ADHD children.